(untitled) (Docentes 2.0 Journal, 2022)
Technology has been gaining prominence because it currently allows processes to occur at any time, facilitating access to a more significant number of learners. The objective of this research was to assess the use of Moodle and Microsoft Teams in designing an Anglophone literature course, favoring the development of writing in learning English as a foreign language through the flipped classroom modality at the university level. The research method was analytical-synthetic under a pragmatic paradigm, with a mixed approach of an exploratory type following a sequential exploratory design. The study was carried out with ninth-semester students. Among the instruments used, a survey was applied to the students, obtaining quantitative data. Interviews were conducted with English teachers and experts using platforms, reaching qualitative data. Likewise, two focus groups were applied. The results were the following: the use of educational platforms effectively provides benefits to the academic community since it is an alternative that offers the possibility of exchanging material, promotes autonomy, feedback, interaction, and collaborative work; facilitates the work of the teacher by obtaining a more active learner, among others. These resources make writing possible due to functions such as the forum, chat, shared documents, peer correction, etc. In addition, supported by the flipped classroom model, it is a feasible option that strengthens virtual education.